Towards a "Sample-In, Answer-Out" Point-of-Care Platform for Nucleic Acid Extraction and Amplification: Using an HPV E6/E7 mRNA Model System. (22nd December 2011) - Gulliksen, Anja; Keegan, Helen; Martin, Cara; O'Leary, John; Solli, Lars A.; Falang, Inger Marie; Grønn, Petter; Karlgård, Aina; Mielnik, Michal M.; Johansen, Ib-Rune; Tofteberg, Terje R.; Baier, Tobias; et al.
Abstract : The paper presents the development of a "proof-of-principle" hands-free and self-contained diagnostic platform for detection of human papillomavirus (HPV) E6/E7 mRNA in clinical specimens. The automated platform performs chip-based sample preconcentration, nucleic acid extraction, amplification, and real-time fluorescent detection with minimal user interfacing. It consists of two modular prototypes, one for sample preparation and one for amplification and detection; however, a common interface is available to facilitate later integration into one single module. Nucleic acid extracts (n = 28 ) from cervical cytology specimens extracted on the sample preparation chip were tested using the PreTect HPV-Proofer and achieved an overall detection rate for HPV across all dilutions of 50%–85.7%. A subset of 6 clinical samples extracted on the sample preparation chip module was chosen for complete validation on the NASBA chip module. For 4 of the samples, a 100% amplification for HPV 16 or 33 was obtained at the 1 : 10 dilution for microfluidic channels that filled correctly. The modules of a "sample-in, answer-out" diagnostic platform have been demonstrated from clinical sample input through sample preparation, amplification and final detection.